Pengaruh Globalisasi Terhadap Rasa Cinta Tanah Air Pelajar di Banyumas - Dinie Anggraeni Dewi; Yhesa Rooselia Listiana (Civiliza Publishing, 2021)
This research discusses the influence of the development of globalization on the love of the homeland of students in Banyumas, which aims to determine how much they understand and how much love their homeland has for the Unitary State of the Republic of Indonesia. The author uses descriptive quantitative research methods, where the authors collect data by sharing a google form link to be filled in by students in Banyumas. As a result, there are several teenagers in Banyumas who admit to being addicted to technology and obsessed with social media. They also claim to know the meaning of love for the country, but in reality they are still confused about implementing the love for their motherland for the nation and the State of Indonesia.